2015
DOI: 10.1016/j.acvd.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil in heart transplant candidates with pulmonary hypertension

Abstract: In patients with pulmonary hypertension related to left ventricular systolic dysfunction, sildenafil seems to improve cardiac haemodynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Five patients were able to proceed with successful OHT and 6 with left ventricular assist device (LVAD). All patients with a PVR <3 Wood units after treatment survived, with survival in the group with PVR >3 being only 44% (41). In addition, hemodynamic parameters such as RV ejection fraction, PVR, and peak oxygen consumption improved in this population of HF patients with WHO group 2 PH with the administration of sildenafil (41).…”
Section: Pde-5 Inhibitors and Guanylyl Cyclase Agonistsmentioning
confidence: 83%
“…Five patients were able to proceed with successful OHT and 6 with left ventricular assist device (LVAD). All patients with a PVR <3 Wood units after treatment survived, with survival in the group with PVR >3 being only 44% (41). In addition, hemodynamic parameters such as RV ejection fraction, PVR, and peak oxygen consumption improved in this population of HF patients with WHO group 2 PH with the administration of sildenafil (41).…”
Section: Pde-5 Inhibitors and Guanylyl Cyclase Agonistsmentioning
confidence: 83%
“…While the use of sildenafil has been studied in HT candidates for the management of PH and RV failure pre-and post-HT, these studies are small and single-center in nature. 39,40 Unpublished data from our center suggests that there is a significantly increased risk of short-term mortality in those patients on high-dose sildenafil (>20 mg TID) compared with those on low-dose or no sildenafil prior to HT.…”
Section: Swan-guided Therapymentioning
confidence: 98%
“…Furthermore, the patient was never initiated on pulmonary vasodilators (specifically sildenafil), as there was improvement in his pulmonary vascular parameters with maximal systemic unloading. While the use of sildenafil has been studied in HT candidates for the management of PH and RV failure pre‐ and post‐HT, these studies are small and single‐center in nature . Unpublished data from our center suggests that there is a significantly increased risk of short‐term mortality in those patients on high‐dose sildenafil (>20 mg TID) compared with those on low‐dose or no sildenafil prior to HT.…”
Section: Commentmentioning
confidence: 99%
“…PAH with ≥3 risk factors for left‐heart disease) . Another registry showed that the use of sildenafil improved haemodynamics in HF patients with post‐capillary PH before heart transplantation . However, the most important randomized trial that tested the administration of PDE5‐I (sildenafil) in 216 patients with HFpEF for 24 weeks did not show any improvement in exercise capacity or clinical status .…”
Section: Do the Various Definitions Of Post‐capillary Pulmonary Hypermentioning
confidence: 99%
“…Selected studies assessing the effect of drugs on cardiopulmonary hemodynamics and clinical endpoints in HF classified according to the studied drug. [34][35][36][37][38][39][40][41][42]…”
Section: Supporting Informationmentioning
confidence: 99%